국방 AI 소요의 중복 최적화를 위한 AI 능력(Capability)의 역할 개념모델 연구 - 박승규; 이중윤; 이주연 (시스템엔지니어링학술지, 2023)
Multidimensional efforts such as budgeting, organizing, and institutionalizing are being carried out for the adoption of defense AI. However, there is little interest in eliminating duplication of defense resources that may occur during the AI adoption. In this study, we propose a theoretical conceptual model to optimize duplication of AI technology that may occur during the AI adoption in the vast defense field. For a systematic approach, the JCA of the US DoD and system abstraction method are applied, and the IMO logical structure is used to decompose AI requirements and identify duplication. As a result of analyzing the effectiveness of our conceptual model through six example defense AI requirements, it was found that the amount of requirements of data and AI technologies could be reduced by up to 41.7% and 70%, respectively, and estimated costs could be reduced by up to 35.5%.
Keywords: Artificial Intelligence; AI Adoption; JCA; Systems Engineering; Requirements Duplication